Effective chemical management for prevention of aflatoxins in maize - LAGOGIANNI, Christina; TSITSIGIANNIS, Dimitrios (Phytopathologia Mediterranea, 2018)
The presence of aflatoxins in maize grain has been an increasing problem in the Mediterranean area, possibly due to climate change such as increased temperatures and extended drought periods. It is therefore important to prevent the growth of aflatoxigenic Aspergillus species in the field. There are no fungicides registered for control A. flavus in maize, so this study investigated the efficacy of azoxystrobin, boscalid, cyprodinil, fludioxonil and cyprodinil + fludioxonil to reduce A. flavus growth, sporulation and aflatoxin production in in vitro, and in maize field studies. Based on in vitro inhibition of mycelial growth, the most effective fungicides were cyprodinil (EC50 < 0.05 μg mL-1) and fludioxonil (EC50 <0.11 μg mL-1), while the least effective was boscalid (EC50 4.35-4.50 μg mL-1). Azoxystrobin almost completely inhibited the conidium germination at > 0.5 μg mL-1. Further evaluation of the fungicides on maize seeds infected with A. flavus demonstrated that all the fungicides reduced conidium production by 76 to 94%, and reduced aflatoxin contamination. In a 2-year field study, application of cyprodinil + fludioxonil reduced A. flavus ear rot severity by 40%, and was the most effective formulation for reducing aflatoxin contamination, by 83%. The other four single ingredient fungicides also decreased aflatoxin production on maize kernels (fludioxonil by 80%, cyprodinil by 75%, boscalid by 74% and azoxystrobin by 67%). Field data from this study provide farmers with a new effective chemical approach to control A. flavus and aflatoxin production in maize within an integrated strategy for management of aflatoxins in maize.